Poor sleep quality and associated factors among adult chronic kidney disease patients - Gela, Yibeltal Yismaw; Limenh, Liknaw Workie; Simegn, Wudneh; Ayenew, Wondim; Chanie, Gashaw Sisay; Seid, Abdulwase Mohammed; Beyna, Alemante Tafese; Esubalew, Dereje; Mitku, Melese Legesse; Mengesha, Assefa Kebad; Melese, Mihret (Frontiers in Medicine, 2024)
Background Poor sleep quality is a common concern in chronic kidney disease (CKD) patients, which can accelerate the progression of chronic renal disease and negatively impact their health-related quality of life, potentially leading to greater morbidity and mortality rates. It can also have an effect on the immune system, cognitive function, and emotional well-being of CKD patients. Furthermore, poor sleep quality may contribute to drug noncompliance and decreased participation in the entire treatment plan. Nonetheless, no research has been undertaken in Ethiopia on the prevalence of poor sleep quality and its associated factors among CKD patients. Objective This study aimed to assess the prevalence of poor quality of sleep and associated factors among chronic kidney disease patients at the University of Gondar Comprehensive Specialized and Felege Hiwot Referral Hospitals in 2020. Methods A cross-sectional study design was implemented at the University of Gondar Comprehensive Specialized and Felege Hiwot Referral Hospitals between February and April 2020. The study participants were chosen through systematic random sampling techniques. The Pittsburgh Sleep Quality Index (PSQI), a validated assessment tool, was utilized to measure sleep quality. A PSQI total score > 5 was used as an indicator of poor sleep quality. Subsequently, the data obtained were entered into Epi Data version 3.0 and then transferred to STATA 14 for analysis. Both bivariable and multivariable binary logistic regression analyses were performed to recognize factors associated with poor sleep quality. In the multivariable logistic regression analysis, variables demonstrating a p-value of ≤0.05 were considered statistically associated to poor sleep quality. Results In this study, 424 CKD patients were included. Among screened CKD patients, 42.9% tested positive for poor sleep quality with a 95% CI (38 to 47%). Independent predictors of poor sleep quality among CKD patients were common mental disorder [AOR = 1.8, 95% CI (1.19–2.89)], anemia [AOR = 2.7, 95% CI (1.71–4.36)], declined eGFR between 60 and 89.9 [AOR = 1.6; 95% CI (2.28–5.54)], 30–59.9 [AOR = 2.6, 95% CI (1.53–4.43)], and ≤ 30 [AOR = 3.8, 95% CI (1.17–12.61)], age > 50 years [AOR = 1.7(1.11–2.69)] and duration of disease 2.9 [AOR = 2.9, 95% CI (1.77–4.90)]. Conclusion In our study, almost 1 out of 2 CKD patients assessed for poor sleep quality tested positive. It was noted that poor sleep quality was more frequent among CKD patients with common mental disorders, anemia, decreased eGFR levels, individuals aged over 50 years, and those with a longer duration of the disease. Consequently, it’s advised to regularly screen these CKD patients for poor sleep quality.